Der Heilige Quirinus von Siscia und der Heilige Martin in Savaria/Stein am Anger/Szombathely - Pillinger, Renate (Mitteilungen zur christlichen Archäologie, 2022)
The present article not only traces the life of the two Pannonian saints Quirinus and Martin in ancient Savaria, but also demonstrates their presence in the modern city of Szombathely. Unfortunately, many questions remain unanswered, such as the translation of Quirinus to Rome or the localisation of a basilica at the porta Scarabatensis. A German translation of the Acta Beati Quirini Episcopi et Martyris is presented for the first time (in the appendix). St. Martin's birthplace cannot be located in the cemetery extra muros, which is why the walls found under the apse of St. Martin’s Chapel by I. Paulovics are probably not the remains of the house where St. Martin was born, but ruther the remnant of the Basilica of Quirinus. In spite of the dense city population today, one can only hope for future excavations.